The Role of Community Participation, Apparatus Capacity, and Monitoring Systems in Improving Village Fund Accountability - Nursapa Indah Damanik; Yenni Samri Juliati Nasution; Nurul Inayah (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of community participation, apparatus capacity, and the monitoring system on the accountability of Village Fund management in Barumun Tengah District, Padang Lawas Regency. Using a quantitative approach with an associative method, this study involved a population of village officials and beneficiaries of the Village Fund. A sample of 60 respondents was selected through a purposive sampling technique. Data were collected via questionnaires and in-depth interviews, then analyzed using multiple linear regression with the help of SPSS version 25. The results showed that partially, community participation, apparatus capacity, and the monitoring system had a positive and significant effect on the accountability of Village Fund management. The monitoring system had the most dominant influence. Simultaneously, the three variables had a significant effect (F count = 40.980 significance 0.000), with a coefficient of determination (R²) of 0.683, which explained 68.3% of the variation in accountability, while 31.7% was influenced by other factors such as leadership, commitment, and public transparency. These findings confirm that increasing accountability in Village Fund management requires synergy between the community, apparatus, and an effective monitoring system. Village governments need to strengthen community participation in deliberations, increase the capacity of officials through ongoing training, and improve transparent and participatory monitoring mechanisms to support more accountable Village Fund governance.